Partial Least Squares Structural Equation Modeling (PLS-SEM) Applications in Economics and Finance - Valls Martínez, María del Carmen; Martín Cervantes, Pedro Antonio (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book includes the 14 articles accepted and published in the Special Issue "Partial Least Squares Structural Equation Modeling (PLS-SEM): Applications in Economics and Finance" of the MDPI journal Mathematics, which encompasses a wide range of topics connected with the theory and applications of PLS-SEM methodology. These topics involve, among others, prediction of stock market investment intention, institutional quality and international competitiveness, governance paradigms and public innovation, information and communication technologies in the supply chain, influence of the ability to absorb information from the environment and proactivity on the company's results, quality management, effects of the corporate social responsibility on financial performance, resource management for the improvement of the healthcare system, and the application of maximum entropy bootstrapping to time series. It is expected that the book will prove worthwhile and helpful for those working in the area of PLS-SEM, regardless of the field of application (economics, finance, marketing, education or other). Applications of higher order constructs, mediating variables, multigroup analysis and the latest advances in applied methodology can all be found in this book.